Heterogeneity of Patients with Intermediate (BCLC B) Hepatocellular Carcinoma: Proposal for a Subclassification to Facilitate Treatment Decisions - Bolondi, Luigi; Burroughs, Andrew; Dufour, Jean-François; Galle, Peter R.; Mazzaferro, Vincenzo; Piscaglia, Fabio; Raoul, Jean Luc; Sangro, Bruno (Seminars in Liver Disease, 2012)
The intermediate stage of hepatocellular carcinoma (HCC) comprises a highly heterogeneous patient population and therefore poses unique challenges for therapeutic management, different from the early and advanced stages. Patients classified as having intermediate HCC by the Barcelona Clinic Liver Cancer (BCLC) staging system present with varying tumor burden and liver function. Transarterial chemoembolization (TACE) is currently recommended as the standard of care in this setting, but there is considerable variation in the clinical benefit patients derive from this treatment.In April 2012, a panel of experts convened to discuss unresolved issues surrounding the application of current guidelines when managing patients with intermediate HCC. The meeting explored the applicability of a subclassification system for intermediate HCC patients to tailor therapeutic interventions based on the evidence available to date and expert opinion. The present report summarizes the proposal of the expert panel: four substages of intermediate HCC patients, B1 to B4.
Keywords: hepatocellular carcinoma; sorafenib; transarterial chemoembolization; radioembolization; Barcelona Clinic Liver Cancer